Understanding How Bereaved Parents Cope With Their Grief to Inform the Services Provided to Them. (April 2017) - Stevenson, Moire; Achille, Marie; Liben, Stephen; Proulx, Marie-Claude; Humbert, Nago; Petti, Antoinette; Macdonald, Mary Ellen; Cohen, S. Robin
Our objective was to develop a rich description of how parents experience their grief in the first year after the death of their child, and how various bereavement follow-up and support services helped them during this time, with the aim of informing follow-up and support services offered to bereaved parents. Our findings situated parents' individual experiences of coping within the social and institutional contexts in which they grieved. In the first year after the death of their child, parents regulated their intense feelings of grief through loss-oriented, restoration-oriented, and/or meaning reconstruction strategies. Often, parents' relationships with others and many of the bereavement follow-up and support services helped them in this regard. This article also explores how the results may aid service providers in accompanying parents in a way that optimizes outcomes for these parents.